The effect of education and awareness on the Quality-of-Life in postmenopausal women - Forouhari Sedigheh; Khajehei Marjan; Moattari Marziyeh; Mohit Mitra; Rad Mozhgan; Ghaem Haleh (Wolters Kluwer Medknow Publications, 2010)
Objectives: Women are one of the most important parts of the family and society, and community health is dependent on provision of the needs of this group. Menopause is one of the most critical stages of life among women. One of the aims of health services for all of the people in the 21 st century is improvement of the quality-of-life. In menopausal women, the term quality-of-life incorporates its physical symptoms such as hot flushes, night sweats and vaginal mucosa dryness. We set out this study in order to evaluate the effect of education on the quality-of-life and the improvement of health standards in menopausal women. Materials and Methods: Sixty-two women aged 44-55 referring to and academic outpatient clinic in Shiraz were selected by simple random sampling, and allocated in two groups. Data was collected using a modified Hildich questionnaire on quality-of-life in menopause stage. Quality-of-life of the subjects (vasomotor, psychosocial, physical and sexual aspects) were evaluated prior to and 3 months after educational intervention. Results: Mean quality-of-life score in study and control groups, prior to education, was 81.7 and 74.8; changing to 75.3 and 75.8, respectively three months after intervention. The study group showed a significant improvement in their quality-of-life (p = 0.001). A significant difference was seen between groups in terms of changing quality-of-life after intervention (p = 0.001). Conclusions: Appropriate training to menopausal women improves their quality-of-life and promotes their health.